2012
DOI: 10.3126/njms.v1i2.6603
|View full text |Cite
|
Sign up to set email alerts
|

Gonococcal infections: The trends of antimicrobial susceptibility of Neisseria gonorrhoeae in Western Nepal

Abstract: Background: Gonorrhea is caused by Neisseria gonorrhoeae, is an important public health problem and is the second most common reportable sexually transmitted bacterial infection. Present study was conducted to determine the antimicrobial resistance pattern of Neisseria gonorrhoeae isolates from various clinical specimens. Methods: This is a hospital based retrospective study conducted at Manipal Teaching Hospital, Pokhara, Nepal. Various clinical specimens (urethral, cervical and conjunctival discharges) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
4
3
0
Order By: Relevance
“…Some isolates were resistant to penicillin (85.7z), ciprofloxacin (88.0z), ofloxacin (97.4z), or tetracycline (89.1z). Our results agree with those of other studies that have shown gonococci that remain susceptible to ceftriaxone, e.g., Nepal (12) and Hungary (13).…”
Section: Discussionsupporting
confidence: 93%
“…Some isolates were resistant to penicillin (85.7z), ciprofloxacin (88.0z), ofloxacin (97.4z), or tetracycline (89.1z). Our results agree with those of other studies that have shown gonococci that remain susceptible to ceftriaxone, e.g., Nepal (12) and Hungary (13).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, N.gonorrhoeae showed 25–50 % resistance rate against ciprofloxacin, tetracycline, ampicillin and erythromycin. This was coherent with studies in Nepal [ 41 ], Port Elizabeth [ 42 ], and Saudi Arabia [ 43 ] where 37.5–42.5 %, 50–94 %, 25 % and 50 % resistance of ciprofloxacin, tetracycline, ampicillin and erythromycin, respectively were noticed. Group B Streptococcus revealed 20 % resistance rate against ciprofloxacin, norfloxacin, erythromycin and clindamycin.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding antimicrobial susceptibility, we observed moderate to high (60-88%) resistance to conventional antimicrobials including ciprofloxacin and cefixime and similar trend of resistance has been reported over the time by many investigators 14,15,16…”
Section: Discussionsupporting
confidence: 88%